RETINITIS PIGMENTOSA: CLINICAL PICTURE AND DIAGNOSTIC INSIGHTS - Qo’ziyev Siddiqjon Rifat o’g’li; Elmurotova Dilnoza Baxtiyorovna (Western European Studies, 2025)
Retinitis Pigmentosa (RP) is an inherited retinal degenerative disorder primarily affecting rod photoreceptors, followed by secondary cone cell loss. The disease manifests clinically with progressive night blindness, peripheral vision constriction, and eventual tunnel vision. As degeneration advances, central vision and color perception are also impaired. Modern diagnostic techniques such as full-field electroretinography (ffERG), spectral-domain optical coherence tomography (SD-OCT), and fundus autofluorescence (FAF) imaging play crucial roles in assessing disease severity and progression. This article summarizes the key clinical manifestations of RP, emphasizing the correlation between photoreceptor degeneration and functional visual loss, and reviews multimodal diagnostic approaches essential for early detection and management
Keywords: Retinitis Pigmentosa; clinical symptoms; night blindness